Plasmon Enhanced Photovoltaic Performance in TiO2-Graphene Oxide Composite Based Dye-Sensitized Solar Cells. (19th August 2015) - Agarwal, Radhe; Sahoo, Satyaprakash; Resto, Oscar; Katiyar, Ram S.
Abstract : Dye sensitized solar cells (DSSCs) have engendered great research interest with promising potentials in solar cell technology for their high power conversion efficiencies. In this study, we report a plasmon enhanced graphene oxide (GO)-based TiO2 -GO-Au composite photo-anode toward the improved performance in our DSSCs. The structural and morphological properties of as synthesized GO and TiO2 -GO-Au composites were investigated using Raman spectroscopy and ultra-high resolution transmission electron microscope (UHRTEM). Photovoltaic performances of DSSC containing TiO2 -GO-Au composite photoanodes were studied on keeping the constant GO concentration (5 μL) and by varying the concentration of Au-nanoparticles (NP) [1, 3, 5 μL]. A systematic increment in the short circuit current density (JSC ) was noticed while incorporating more Au NP to the photoanode probably due to the increased light absorption, higher optical path of absorbed light and faster electron transfer as a combined effect of GO and Au NP. Thus, a significant enhancement in the overall photovoltaic performance was observed in DSSCs with TiO2 -GO-Au composite photoanode.